Strategi Pemasaran Digital untuk Meningkatkan Konversi Penjualan pada Bakso Malang Jezzy - Jose Daniel Sirait; Muhammad Fajr Al Ghazi; Deru R. Indika (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This final project is created to fulfill the graduation requirements for a Bachelor's degree in Digital Marketing at FEB UNPAD. This final project is designed to help Bakso Malang Jezzy increase its sales, which have declined over the past 3 years. The researcher hopes that this project can provide a reference for food and beverage business owners to improve conversion rates using digital marketing strategies. Bakso Malang Jezzy has 18 branches spread across Bekasi City and Bogor Regency. Bakso Malang Jezzy operates differently from other Bakso Malang vendors by using a buffet technique. Additionally, the production house for all Bakso Malang Jezzy branches is centralized at Jl. Payangan Mess. Al, Jatisari, Jatiasih, Bekasi, West Java, which serves as the meat processing and quality control center. The proposed digital marketing strategy includes the use of social media such as TikTok and Instagram, as well as search engine optimization and content marketing to increase visibility and customer engagement. With this strategy, Bakso Malang Jezzy is expected to increase sales conversions and strengthen its market position. The theoretical benefits of this project include contributions to the digital marketing literature, while the practical benefits include increased sales and brand positioning for Bakso Malang Jezzy.